If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -2y = 17 Solving -3x + -2y = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. -3x + -2y + 2y = 17 + 2y Combine like terms: -2y + 2y = 0 -3x + 0 = 17 + 2y -3x = 17 + 2y Divide each side by '-3'. x = -5.666666667 + -0.6666666667y Simplifying x = -5.666666667 + -0.6666666667y
| y-32=-10 | | p^2-2pq+q^2=0 | | x^2-6x^2-9= | | 30-6x=6-3x | | Y=X^2+9x+18 | | -16x^2-60x+6=0 | | x^2+16x-78=0 | | 18s^3=-50s | | 2x-y+17=0 | | 5-5x=0 | | x^2+10x-119=0 | | 5-9=3 | | -5+(-15d+1)=2(7d-16)-d | | 21x-5-16x+2=17x-9-12x+15 | | 6x-16=-96 | | 3(c+5)= | | 4r=-28 | | 23b-19b= | | (10x+3)=(15x-7) | | 15x+14y+27x=0 | | 14x-7=12x+3 | | 9y+11y= | | y=100 | | (4t+16)=(5t-21) | | a-3.5=19.5 | | x=4-2x | | 2a-21.2=a+1.8 | | 9x-8+4x=13x-8 | | 3(2x+5)=2(4x-5)3x | | X(x-15)=35 | | 4n+5(7n-3)=9(n-5) | | (6a-4)=(4a+36) |